Sudan virus disease super-spreading, Uganda, 2022 - Komakech, Allan; Shannon, Whitmer; Izudi, Jonathan; Muruta, Allan N.; Harris, Julie R. (BMC Infectious Diseases, 2024)
On 20 September 2022, Uganda declared its fifth Sudan virus disease (SVD) outbreak, culminating in 142 confirmed and 22 probable cases. The reproductive rate (R) of this outbreak was 1.25. We described persons who were exposed to the virus, became infected, and they led to the infection of an unusually high number of cases during the outbreak.